2018
DOI: 10.1093/jamia/ocy132
|View full text |Cite
|
Sign up to set email alerts
|

AMIA Board White Paper: AMIA 2017 core competencies for applied health informatics education at the master’s degree level

Abstract: This White Paper presents the foundational domains with examples of key aspects of competencies (knowledge, skills, and attitudes) that are intended for curriculum development and accreditation quality assessment for graduate (master’s level) education in applied health informatics. Through a deliberative process, the AMIA Accreditation Committee refined the work of a task force of the Health Informatics Accreditation Council, establishing 10 foundational domains with accompanying example statements of knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…This innovative program aims at involving both medical students and doctors in the design of clinical decision support system (under the supervision of the medical informatic team). This work demonstrated the need to develop such digital health program in medical curriculum, and not only at master's degree level [8,9].…”
Section: Discussionmentioning
confidence: 94%
“…This innovative program aims at involving both medical students and doctors in the design of clinical decision support system (under the supervision of the medical informatic team). This work demonstrated the need to develop such digital health program in medical curriculum, and not only at master's degree level [8,9].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, a Could-IoT (a cloud-based Internet of Thing) based sensing service to monitor the health of elderly people has also been produced by Neagu et al [15], while Motulsky et al [16] have studied and reported the usage of mobile devices for inpatient rounding and handoffs. Some researchers even give their focus to the development of MI's education, as can be found in the research of Saranto et al [17], Valenta et al [4], Cummings et al [5], and Jaspers et al [18]. All of these show the significant contribution offered by MI to the health of global society.…”
Section: Importance Of Medical Informaticsmentioning
confidence: 99%
“…AMIA (American Medical Informatics Association) for example, tends to use the terms of biomedical informatics and healthcare informatics rather than medical informatics, which is used as a parallel term to other subareas, such as nursing informatics and dental informatics [2]. Other researchers have adopted the terms and definition given by AMIA, such as Sweeney [3], Valenta et al [4], and Cummings et al [5]. Meanwhile, the others prefer to use the medical informatics term as can be found in the works of Mihalas et al [6], Collen and Shortliffe [1], and Wyatt and Liu [7].…”
Section: Introductionmentioning
confidence: 99%
“…Biomedical informaticians use biomedical data, information, and knowledge for scientific inquiry, problem-solving, and decision-making to improve human health. 6 , 7 However, when intentionality in achieving representation and inclusivity is missing from the biomedical informatics workforce, key insights and viewpoints are also missing in the design, implementation, and evaluation of technologies. It also increases the potential for unintentional incorporation of biases into the design of technology-based interventions.…”
Section: Introductionmentioning
confidence: 99%